Education on Career Opportunities for Accounting Graduates in the Digital Era at SMA Negeri 1 Airmadidi - Pesak, Pricilia Joice; Pratiwi, Ananta Dian (LPPM UIKA Bogor, 2024)
In the digital era, technological advances have changed many things in various fields of work, including accounting. As a preparation for high school students to face these developments and provide an understanding of career opportunities in the world of accounting, a comprehensive educational activity was carried out. The purpose of this activity is to increase students' understanding of the duties and responsibilities of accountants in the digital age, introduce a variety of career opportunities that can be pursued by accounting graduates, foster students' interest in continuing higher education in the Accounting Department, and provide basic knowledge and skills relevant to the latest technological developments in accounting. The methods of this service include preparation, implementation, and evaluation. Through this activity, high school students' understanding of career opportunities for accounting graduates increased, and interest in continuing higher education in the Accounting Department of Universitas Negeri Manado increased.